2016
DOI: 10.3390/polym8040162
|View full text |Cite
|
Sign up to set email alerts
|

Smart Homopolymer Microgels: Influence of the Monomer Structure on the Particle Properties

Abstract: Abstract:In this work, we compare the properties of smart homopolymer microgels based on N-n-propylacrylamide (NNPAM), N-isopropylacrylamide (NIPAM) and N-isopropylmethacrylamide (NIPMAM) synthesized under identical conditions. The particles are studied with respect to size, morphology, and swelling behavior using scanning electron and scanning force microscopy. In addition, light scattering techniques and fluorescent probes are employed to follow the swelling/de-swelling of the particles. Significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 65 publications
4
59
0
Order By: Relevance
“…9,10 At low temperatures the solution structure of microgel particles can be described by the "fuzzy-sphere" model, which exhibits a core-region with a constant density and a fuzzy shell where the density follows a sigmoidal decay. 11 Here, a more complex nanoscale architecture of the microgel particles is investigated: microgel particles based on N-isopropylmethacrylamide (NIP-MAM) (VPTT in water $42 C) 12 are used as seed particles for a second synthesis step, where N-n-propylacrylamide (NNPAM, VPTT of crosslinked homopolymer microgels in water: $22 C) 12,13 is polymerized in the presence of the collapsed seed particles leading to a core-shell structure. 14,15 A peculiar feature of these particles is the linear dependence of the particle size on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 At low temperatures the solution structure of microgel particles can be described by the "fuzzy-sphere" model, which exhibits a core-region with a constant density and a fuzzy shell where the density follows a sigmoidal decay. 11 Here, a more complex nanoscale architecture of the microgel particles is investigated: microgel particles based on N-isopropylmethacrylamide (NIP-MAM) (VPTT in water $42 C) 12 are used as seed particles for a second synthesis step, where N-n-propylacrylamide (NNPAM, VPTT of crosslinked homopolymer microgels in water: $22 C) 12,13 is polymerized in the presence of the collapsed seed particles leading to a core-shell structure. 14,15 A peculiar feature of these particles is the linear dependence of the particle size on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their large surface area for multivalent bioconjugation, flexibility, and softness, superior colloidal stability, and stimuli‐responsive behavior enable them as a unique and versatile platform for various biomedical applications such as drug delivery, imaging, DNA or small interfering RNA (siRNA) delivery, and tissue regeneration . Several review articles have been reported in the literature and the readers are referred to them for detailed information on different fundamental aspects of microgels …”
Section: Introductionmentioning
confidence: 99%
“…Due to the hydrophilic property below the lower critical solution temperature (LCST), PNIPAM shells can increase the colloidal stability of nanoparticles in aqueous solution and help form an array with distance between each of the hybrid nanoparticles when they are dried on different substrates. [32][33][34][35][36][37][38] For instance, Liz-Marzán et al 39 and Karg et al 40 successfully synthesized hybrid systems by encapsulating gold and silver nanoparticles inside PNIPAM shells, respectively. Due to the modification of the PNIPAM shell, the colloidal stability of the nanoparticles was improved and the monolayer arrays of the particles can be obtained.…”
Section: Introductionmentioning
confidence: 99%